1993
DOI: 10.1007/bf01686458
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the expression of c-fos, c-jun and c-erbB-1 oncogene products in human squamous cell lung carcinomas

Abstract: The expression of the oncogenes c-fos, c-jun, c-myc, c-erbB-1 and c-erbB-2 at the protein level was analyzed in squamous cell lung carcinomas of 121 patients by means of immunohistochemistry. Patients with overexpression of proteins encoded by the oncogenes c-fos, c-jun and c-erbB-1 had significantly shorter survival times than these without overexpression of these oncogene products (c-fos: p = 0.009; c-jun: p = 0.029; c-erbB-1: p = 0.018). No significant correlations were found between the expression of c-myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 14 publications
5
28
1
1
Order By: Relevance
“…Investigations focussing on abnormalities of oncogenes (e.g. Ki-ras, c-fos, c-jun and c-erb B1) and tumor suppressor genes (p53, Rb), especially in primary tissues of NSCLC, are still limited (Rodenhuis et al, 1987(Rodenhuis et al, , 1988Slebos et al, 1990;Volm et al, 1993;Bongiorno et al, 1994;Takahashi et al, 1989;Harbour et al, 1988). Various members of the family of protein kinases are involved in the development of human neoplasms, but the knowledge of their role in primary NSCLC is also restricted (Bishop et al, 1991;Strebhardt et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations focussing on abnormalities of oncogenes (e.g. Ki-ras, c-fos, c-jun and c-erb B1) and tumor suppressor genes (p53, Rb), especially in primary tissues of NSCLC, are still limited (Rodenhuis et al, 1987(Rodenhuis et al, , 1988Slebos et al, 1990;Volm et al, 1993;Bongiorno et al, 1994;Takahashi et al, 1989;Harbour et al, 1988). Various members of the family of protein kinases are involved in the development of human neoplasms, but the knowledge of their role in primary NSCLC is also restricted (Bishop et al, 1991;Strebhardt et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Another unsolved problem is the association between HER2 status and prognosis in lung cancer patients. Overexpression of the HER2 protein is associated with shorter survival in some, 1,5,16 but not all, 4,6,17,18 reports. Overexpression of p185 HER2 was evaluated by IHC in those studies.…”
mentioning
confidence: 99%
“…Immunohistochemical studies have reported EGFR overexpression in 22 -81% of NSCLC tumours depending on the antibody used and cut point that defines overexpression (Veale et al, 1987;Volm et al, 1993;Pfeiffer et al, 1996;Cornianu and Tudose, 1997;Pastorino et al, 1997;Rusch et al, 1997;Fontanini et al, 1998;Greatens et al, 1998;D'Amico et al, 1999;Fu et al, 1999;Cox et al, 2000;Ohsaki et al, 2000;Selvaggi et al, 2002;Hirsch et al, 2003;Kanematsu et al, 2003;Mukohara et al, 2003;Onn et al, 2003). The majority of these studies have failed to demonstrate an association with prognosis (Table 1).…”
mentioning
confidence: 99%